The First Record of Anax parthenope (Selys, 1839) (Odonata: Aeshnidae) from the Outskirts of Jamshedpur, Jharkhand, India - Raja Ghosh; Md Abu Imran Mallick; Shaba Alam Ansari (Jurnal Pijar MIPA, 2026)
Odonates are widely recognized as effective bioindicators of freshwater ecosystem health, yet their diversity and distribution remain inadequately documented in several parts of eastern India. Anax parthenope (Selys, 1839) (Odonata: Aeshnidae), a broadly distributed species across Asia, Europe, and Africa, has limited confirmed records from this region. The present study aims to document the first confirmed occurrence of A. parthenope from the outskirts of Jamshedpur, Jharkhand, India. An adult male was opportunistically observed and photographed near a semi-permanent freshwater body at Kudada village (22.7076° N, 86.2033° E) in October 2020. Species identification was achieved through comparative morphological analysis using standard taxonomic keys, focusing on diagnostic characters of the thorax, abdomen, and anal appendages. This record represents a new locality for the species in Jharkhand and extends its known distribution within eastern India. The finding underscores the ecological value of peri-urban wetlands as habitats for odonates and highlights the need for systematic, long-term surveys to improve baseline data on odonate diversity and support freshwater biodiversity conservation in the region.